Phylogenetic position of the northern pika Ochotona hyperborea in Hokkaido, Japan based on mitochondrial COI sequences - Sakiyama, Tomoki; Kamiyama, Shumpei; Kawai, Kuniko; Ohari, Yuma; Matsuno, Keita; Ohdachi, Satoshi D. (Mammal research, 2025)
The northern pika Ochotona hyperborea is found in eastern Eurasia including the island populations in Sakhalin and Hokkaido. Taxonomically, the population in Hokkaido, Japan is treated as a subspecies O. h. yesoensis . However, the phylogenetic position of the Hokkaido population has not been thoroughly assessed because only one Hokkaido individual has been used in previous studies to analyze its genetic relationships with other local populations. In the present report, we collected four pika individuals from Hokkaido and examined their phylogenetic position within the species based on nucleotide sequences of the mitochondrial cytochrome c oxidase subunit 1 gene. All four Hokkaido individuals had an identical sequence and were clustered into a monophyletic group with populations from Sakhalin, Khabarovsk, and Primorsky. This finding supports the previous results that the northern pika of Hokkaido belongs to the southeastern population of this species. Within this clade, Hokkaido individuals formed their own clade, suggesting that the Hokkaido population forms a taxonomically independent unit. Our results also suggest that the Hokkaido population may hold low genetic variation, but limited sampling and use of a single marker warrant cautious interpretation. Broader sampling and additional markers are needed to confirm this pattern.